Online news : journalism and the Internet - Allan, Stuart, 1962- (Open University Press, 2006)
Providing an analysis of online news, this book offers insights into key debates concerning the ways in which journalism is evolving on the internet, devoting particular attention to the factors influencing its development. This book shows how the forms, practices and epistemologies of online news are conventionalized.